Changing characteristics of the caste system in India - Sharma, D.A.P. (Journal of Oriental Studies, 2021)
In India, during the last three decades, the caste system’s characteristics have changed significantly. The caste system has never been an uncontested reality in India. The tradition of resistance to the caste system and the sentiment of reform about it are as old as the caste system’s history. The caste (Jati) system has been transformed under the ruling elites from ancient to modern times. However, multiple socioeconomic and political factors are behind the changes that have come after India’s independence. But, the most significant changes have occurred after 1991. The unexpected changes that have come in the last three decades are different in many ways than before. The market-driven new economy, rise of caste identity, access to quality education, and empowerment schemes have made the change possible. This paper explores the changing facets of the Indian caste system, factors of change, and its impact on Indian socio-political life in contemporary India. Key words: Varna, Jan, Jati, Dalit, Gunas, Varna ashram-Dharma, Dwij.